PEMETAAN TINGKAT KEKRITISAN UNTUK DAERAH RESAPAN (WILAYAH STUDI KASUS KOTA PAREPARE) - Uca Sideng; Sukri Nyompa; Novita Citra Rahayu (UNIVERSITAS NEGERI MAKASSAR, 2021)
High population growth, especially in urban areas, increases community needs which trigger land use changes. This causes a decrease in the quality and carrying capacity of the land which has an impact on reducing the rainwater catchment area. One of the problems that often occurs in urban areas is that infiltration conditions are no longer optimal in storing water, causing rainwater to pool on the surface and flooding occurs. The development of remote sensing technology and geographic information systems has made it possible to study the spatial pattern of critical distribution of water catchment areas in a wide scope. This study aims to determine the condition of the potential and actual catchment areas, as well as the criticality level of the water catchment area in the City of Parepare. The method used is scoring and overlaying the parameters of slope, rainfall, and soil type to produce a map of potential catchment areas. The map of the actual catchment area condition was obtained based on the interpretation of the sentinel-2 image. The two resulting maps were then compared to determine the criticality level of the catchment area in Parepare City. The results show that Parepare City has a potential infiltration condition which is dominated by a small potential area of 69.07 km2 and an actual catchment area which is dominated by a rather large infiltration capacity of 30.47 km2. The most dominant criticality level in Parepare City is both an area of 59.24 km2 which is randomly distributed.